Validation of the Netherlands physical activity questionnaire in Brazilian children - Reichert Felipe F; Bielemann Renata M; Paniz Vera MV; Gigante Denise P (BMC, 2011)
Abstract Background Physical activity instruments can be subjective or objective. There is a need to assess the reliability of these instruments, especially for researches in children. The aim of this study was to determine the validity of the Netherlands Physical Activity Questionnaire (NPAQ). Methods Population under study were Brazilian children aged 4 to 11 years old, enrolled in a population-based study. Data collection took place in two distinct moments: 1) application of the NPAQ by face-to-face interviews with mothers' children and 2) utilization of accelerometers by children as the reference method. GT1M Actigraph accelerometer was worn for five consecutive days. Validity analyses were performed by sensitivity and specificity and ROC (Receiver Operator Characteristic) curve. Results Two hundred and thirty nine children participated in both phases of the study. A total of 73.2% children achieved the recommendation of 60 min/day of moderate to vigorous physical activity. The mean and median of the NPAQ score were 25.5 and 26, respectively. The score ranged from 7 to 35 points. The correlation coefficient between the NPAQ and the time spent in moderate to vigorous physical activities was 0.27. Based on the area under the ROC curve, the median value presented the best indicators of sensitivity (59.4%) and specificity (60.9%), and the area under curve was 0.63. The predictive capacity of the NPAQ to identify active children was high regardless the cut-off point chosen. This capacity was even higher if the score was higher than 30. Conclusions Based on sensitivity and specificity values, the NPAQ did not show satisfactory validity. The comparison of the reliability of the NPAQ with other instruments is limited, but correlation coefficients found in this study are similar to others. Physical activity level of children estimated from the NPAQ must be interpreted cautiously, and objective measures such as accelerometers should be encouraged.